Interannual Variation in Phytoplankton Community Driven by Environmental Factors in the Northern East China Sea - Sun, Yanxu; Youn, Seok-Hyun; Kim, Yejin; Kang, Jae Joong; Lee, Dabin; Kim, Kwanwoo; Jang, Hyo Keun; Jo, Naeun; Yun, Mi Sun; Song, Sang-Keun; Lee, Sang Heon (Frontiers in Marine Science, 2022)
The relative importance of interannual environmental changes in shaping phytoplankton community structure remains unclear in the East China Sea (ECS), which is the largest marginal sea in the western North Pacific Ocean. Based on high-performance liquid chromatography (HPLC) analysis of a variety of photosynthetic pigments, we investigated spatiotemporal variations in the phytoplankton community in the northern East China Sea (NECS) from 2018 to 2020 to understand biomass and compositional responses to environmental conditions in a complex current system. Correlation heatmaps and generalized additive models (GAMs) were used to explore the variations in major phytoplankton groups and their relationships to temperature, salinity, depth, and nutrients. The results indicated that the phytoplankton community structure was significantly different between 2018/2019 and 2020. Under the conditions of high dissolved inorganic nitrogen (DIN) and low dissolved inorganic phosphate (DIP) concentrations in winter 2020, cryptophytes replaced diatoms as the dominant species and were observed for the first time in this study area. Dinoflagellates predominated throughout the euphotic zone in spring 2020, and statistical analysis showed that dinoflagellates tended to prevail at low DIP and high DIN conditions compared with diatoms. Summer was the only season with strong water stratification that reoccurred every year, and diatoms were mainly concentrated at nutrient-enriched 1% light depths in the summers of 2018/2019. However, a large amount of Changjiang River Diluted Water (CDW) from the surface and western part of the study area affected all sampling sites eastward to 126°E in 2020, allowing diatoms to be dominant at 100% and 30% light depths in the westernmost stations in the NECS. In autumn 2020, diatoms decreased significantly because of DIP-limited environmental conditions and were replaced by small phytoplankton. Under expected warming ocean scenarios with human-induced nutrient inputs, small phytoplankton will become dominant, while spring dinoflagellate blooms will occur more frequently in the NECS. International monitoring programs for marine ecosystems are currently needed in the ECS.